2018
DOI: 10.1002/1873-3468.13094
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversification of the kinesin‐14 family in land plants

Abstract: In most eukaryotes, cytoplasmic dynein serves as the primary cytoskeletal motor for minus-end-directed processes along microtubules. However, land plants lack dynein, having instead a large number of kinesin-14s, which suggests that kinesin-14s may have evolved to fill the cellular niche left by dynein. In addition, land plants do not have centrosomes, but contain specialized microtubule-based structures called phragmoplasts that facilitate the formation of new cell walls following cell division. This Review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 116 publications
3
17
0
Order By: Relevance
“…However, in vks1, cells at different phases of division were easily observed (Supplemental Figure 9), suggesting that mitosis in vks1 slowed down, which in turn reduced early endosperm cell proliferation (Figure 8). In addition, our data also suggested that VKS1 plays a crucial role in spindle formation and chromosome separation in plants (Figure 6), which is consistent with prior studies on plant kinesin-14s (Chen et al, 2002;Ambrose and Cyr, 2007;Higgins et al, 2016;Dawe et al, 2018;Gicking et al, 2018). The CC domain in the VKS1 N terminus is responsible for localization to MTs (Figure 3H), and the motor in the C terminus generates opposing forces on the spindle MTs, thereby pulling the daughter chromosomes equally to opposite poles of the cell.…”
Section: Vks1 Is Essential For Mt Organization In Mitosis and Cytokinsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in vks1, cells at different phases of division were easily observed (Supplemental Figure 9), suggesting that mitosis in vks1 slowed down, which in turn reduced early endosperm cell proliferation (Figure 8). In addition, our data also suggested that VKS1 plays a crucial role in spindle formation and chromosome separation in plants (Figure 6), which is consistent with prior studies on plant kinesin-14s (Chen et al, 2002;Ambrose and Cyr, 2007;Higgins et al, 2016;Dawe et al, 2018;Gicking et al, 2018). The CC domain in the VKS1 N terminus is responsible for localization to MTs (Figure 3H), and the motor in the C terminus generates opposing forces on the spindle MTs, thereby pulling the daughter chromosomes equally to opposite poles of the cell.…”
Section: Vks1 Is Essential For Mt Organization In Mitosis and Cytokinsupporting
confidence: 92%
“…The kinesin-14 subfamily is greatly expanded in plants, with 20 members in Arabidopsis (Arabidopsis thaliana), 16 in rice (Oryza sativa), and 21 in maize (Supplemental Figure 1; Supplemental File), whereas only four are found in the human genome (Richardson et al, 2006). Plant kinesin-14 motors are involved in spindle morphogenesis, MT-based trafficking, chromosome segregation, chloroplast distribution, and plant-specific phragmoplast formation (Lee et al, 2015;She and Yang, 2017;Gicking et al, 2018). Arabidopsis ATK1, the first kinesin-14 protein discovered in plants, primarily functions in spindle morphogenesis and chromosome segregation during meiosis (Chen et al, 2002;Marcus et al, 2002), whereas Arabidopsis ATK5 is required for mitotic spindle pole formation (Ambrose and Cyr, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this study provides a comprehensive view on the roles of Kinesin-13 and -8 in a single plant species. Furthermore, our results reinforce the emerging view that the kinesin superfamily is well conserved in plants but have diverged in their function (Gicking et al, 2018; Nebenfuhr and Dixit, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…This raises an additional level of regulation of α-Aurora kinases. The presence of a larger number of kinesin genes in plant genomes, in comparison to animals or humans [31,32] can explain the diversity of TPXL isoforms in the B group. At the same time, the reason for such evolutionary separation of the TPXL family based on functionality remains unclear.…”
Section: Diversity Of Tpx In Plantsmentioning
confidence: 99%